+0  
 
+1
60
1
avatar+17 

Let u and v be real numbers such that

\(\begin{align*} u^3 - 3uv^2 &= 259, \\ 3u^2 v - v^3 &= -286. \end{align*}\)

Find \(u^2 + v^2\)

 Feb 28, 2020
edited by CCjump21  Feb 28, 2020
 #1
avatar+109499 
+3

u^3  - 3uv^2  =  259

3u^2v  - v^3   =  -286

 

u( u^2 - 3v^2)  =  259   (1)

v(3u^2 - v^2)  =  -286   (2)

 

Note  that  a possible  factorization  of  259  is   7 * 37

 

Letting  u   =  7

Then

7 ( 3*7^2 - v^2)  = 259     which implies that

u^2  - 3v^2  =  37

7^2  -  3v^2  = 37

49  - 3v^2  =  37

12 =  3v^2

4 =  v^2

v =  2   or  v  = -2

 

So  if   u =  7  and  v   = 2

Then

2 ( 3*7^2 - 2^2)   >  0      so  v = 2   isn't valid  for (2)

 

If  u = 7  and  v  = -2   then 

-2 ( 3*7^2  - (-2)^2 )   =   -2 ( 147 - 4)  = - 2 ( 143)  =  -286   

 

So

 

u = 7      v  =  -2

 

u^2  + v^2   =   7^2  + (-2)^2   =  49 + 4   =  53

 

 

 

cool cool cool

 Feb 28, 2020

31 Online Users

avatar